Accuracy of 6 Commercially Available Activity Monitors in Measuring Heart Rate, Caloric Expenditure, Steps Walked, and Distance Traveled. Issue 4 (October 2019) - Boolani, Ali; Towler, Christopher; LeCours, Baley; Blank, Holly; Larue, John; Fulk, George
Abstract : Purpose: The purpose of this study was to determine the accuracy of 5 different commercially available activity monitors (AMs) and 1 smartphone application in identifying mean number of steps, mean distance traveled, estimated caloric expenditure, and heart rate (HR). Methods: Subjects (N = 120) performed two 6-minute walks (MWs), one at a comfortable pace (C6MW) and the other at a fast pace (F6MW), around an indoor track wearing all 6 AMs and a StepWatch Activity Monitor in the community. Accuracy and agreement between AM-estimated metrics and actual metrics were examined using the intraclass correlation coefficient (ICC2, 1 ) and Bland–Altman technique (BAM). Results: The ICC2, 1 and BAM varied for all 3 conditions with the Fitbit Zip being the most accurate. Conclusions: The AMs exhibited varying degrees of accuracy for identifying steps, calories expended, HR, and distance walked across all different walking conditions. No single AM was accurate across conditions or metrics. Clinicians should be cautious when using data from these AMs to estimate patient activity levels.